Partly deepithelialised palatal graft for the treatment of deep-wide palatal recession defect: simplified protocol with 18-month follow-up. Issue 11 (4th November 2020) - Parashar, Amit; Roy, Indranil Deb; Gupta, Arpit
Abstract : Advances in periodontal plastic surgical procedures have led to achieve predictable root coverage outcomes for the recession defects. However, little has been reported and emphasised over management of palatal recession defects. The root coverage surgical procedures used for coverage of palatal recession defect are technically challenging in terms of accessibility and graft coverage. The purpose of this report is to describe a surgical technique used to manage deep-wide palatal recession defect. The technique uses partly deepithelialised palatal graft that is designed to approximately fit the defect site. This is employed for prolonged protection of the underlying healing process. This case report is unique in terms of treatment of deep (9.0 mm), wide (6.0 mm) palatal recession defect and its long-term follow-up for 18 months.